Implementasi Konsep Kepemimpinan (Qowwamah) Kh. Abu Zaen Syamsudin Di Pondok Pesantren Assalaam Post - Ismail Ismail; Azi Ahmad Tadjudin; Sofia Gussevi (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study examines the implementation of the Qowwamah concept by KH. Abu Zaen Syamsudin at the Assalaam Post Islamic Boarding School in Subang, West Java. The study aims to understand how Qowwamah principles are applied in family leadership and the management of the boarding school. The method used is descriptive qualitative with data collection techniques including in-depth interviews, participatory observation, and documentation. The results indicate that KH. Abu Zaen successfully implements Qowwamah by emphasizing moral responsibility, spirituality, and justice in decision-making. The implementation of Qowwamah has a positive impact not only on family welfare and harmony but also on the management of the boarding school and social interactions within the community. The conclusion of this study is that Qowwamah can serve as an effective Islamic leadership model in Indonesia's multicultural context, with implications for the development of Islamic studies that are more responsive to social and educational needs.